Mechanical properties of self-compacting concrete at different curing conditions - Caliskan, S.; Turk, K.; Yazicioglu, S. (Thomas Telford Services Ltd, 2005)
The paper reports an experimental investigation carried out to examine the effects of curing methods on the mechanical properties of self-compacting concrete (SCC). Portland cement (PC) concrete and two types of SCC, i.e. SCC-I with fly ash (FA30%/70%PC) and SCC-II with silica fume (SF10%/90%PC) were used in the study. The specimens were cured in three different curing methods (namely standard 20 °C water, sealed and air cure) for the periods of 3, 7, 14 and 28 days. Average of 3 specimens was tested for each concrete property (compressive strength, tensile strength). The results indicated that all concretes cured at water always gave the highest values followed by those cured as sealed and in air irrespective of age of concrete and test method. For both compressive and tensile strength tests, the SCC-II gave the highest values followed by SCC-I and then PC concrete for all curing periods and conditions.
2005 International Congress - Global Construction: Ultimate Concrete Opportunities -- 5 July 2005 through 7 July 2005 -- Dundee, Scotland -- 66969
Keywords: Compressive strength; Curing; Fly ash; Self-compacting concrete; Silica fume; Tensile strength